Humidified micro gas turbines for domestic users: An economic and primary energy savings analysis. (15th December 2016) - Montero Carrero, Marina; De Paepe, Ward; Bram, Svend; Musin, Frédéric; Parente, Alessandro; Contino, Francesco
Abstract: Micro Gas Turbines (mGTs) offer valuable advantages for small-scale Combined Heat and Power (CHP) production compared to reciprocating Internal Combustion Engines (ICEs): lower maintenance costs per kWhe, cleaner exhaust, lower vibration levels and concentration of the residual heat in a single source (the exhaust gases). Nevertheless, mGTs have lower electrical efficiencies, fact that has prevented them from penetrating in the CHP market. Hot liquid water injection—by means of a saturation tower within the micro Humid Air Turbine (mHAT) cycle—allows both improving the flexibility of heat production and the electrical efficiency of mGTs; two qualities that if enhanced would increase the economic feasibility of the technology. Although the advantages of mHAT technology have been proven from a thermodynamic point of view, its economic performance has not yet been fully investigated. This paper presents a comparison of the economic profitability and the primary energy savings of an mGT, an ICE and an mHAT unit operating in real network conditions. Our aim is to investigate whether the increase in flexibility and electrical efficiency, achieved when transforming an mGT into an mHAT, allows this technology to economically outperform ICEs. Results show that the three units are viable in scenarios with high electricity and low natural gas prices. For the cases in which investment is feasible, the revenues with mHAT are the highest: thanks to their flexibility in heat generation, mHAT units are able to run all year long. On the other hand, the greatest primary energy savings are achieved with ICE units—which have the highest overall efficiencies—while mHAT savings are substantially lower. Highlights: We analyse the economics and primary energy savings of an ICE, an mGT and an mHAT. We consider hourly heat and electricity demand profiles and 25 price scenarios. Our analysis is carried out for two domestic users with distinctive demand profiles. If the investment is feasible, mHAT always economically outperforms the mGT and ICE. All technologies offer positive energy savings, qualifying as high-efficiency cogeneration.